The Routledge international handbook of drug-related death bereavement - Stroebe, Margaret S.; Dyregrov, Kari; Titlestad, Kristine Berg (New York, NY : Routledge, 2024)
"This handbook provides a comprehensive overview of drug-related death bereavement, to increase understanding and help direct scientific research, with contributions from across the globe. It is the first comprehensive, cross-cultural, multidisciplinary review of research on drug-related death (DRD) bereavement. Chapters cover the impact of DRD at individual, family, cultural, and societal levels, and topics include working with families following drug-related loss, understanding parental grief, drug policy, and the importance of cultural contexts. This handbook will increase understanding of DRD bereavement and contribute to support for DRD bereaved persons and those who care for them professionally and personally. It is essential reading for professionals and academics in the field as well as anyone affected by drug-related death"--
Keywords: Drug abuse -- Psychological aspects; Drug addicts -- Family relationships; Bereavement; PSYCHOLOGY / Mental Health